DIGITAL MARKETING OF FISH FARMING PRODUCTS IN BUCKETS AS AN ENVIRONMENTALLY FRIENDLY BUSINESS MEDIUM IN THE CIKANCAS VILLAGE AREA - Moch Sigit Gunawan; Fatina Rizka Sahila; Yoga Permana Sopyan; Edwin Gunawan; Syakira Ramadhani (Ann Publisher, 2026)
Abstract Background. The community service program carried out by the participants of KKN-T (Thematic Real Work Lecture) of Gunung Jati Swadaya University is a contribution of students to apply the knowledge that has been obtained during the first lecture. This activity is a manifestation of the implementation of the Tridharma of Higher Education, namely organizing education, conducting research, and community service. Aims. The research aims to develop the potential of villages for economic growth through environmentally friendly programs, namely, aquaponics or fish and plant cultivation in buckets. Aquaponics is a system of waste utilization as aquaculture media with hydroponics to cultivate aquatic livestock such as fish that uses the rest of the livestock's metabolism as a support for plant fertility. The high number of people in rural areas is one of the factors that can support food security programs through fish farming products in buckets, as the effectiveness of minimal land in every house. Methods. This study used research development to examine the cultivation programs process in a descriptive, evaluative, and experimental manner to optimize harvest and sales through digital systems. Result. The research will result in the success of village service activities by providing a simulation of a new business, fish cultivation in buckets, to support the economic sector of villagers. Conclusion. Cikancas Village was chosen because it has potential in the fields of agriculture and livestock, but still faces the challenge of low public awareness of entrepreneurship and digital marketing of local products. Through the One Village One Product (OVOP) concept, KKN-T students initiated the Fish Cultivation in Bucket (Budikdamber) program as an innovative solution to improve the village economy. Implication. This activity has a positive impact, both in terms of household food security and in increasing residents' income. The community is able to practice Budikdamber independently and get double benefits from the fish and vegetable harvest.